Estrategias lúdicas para mejorar la psicomotricidad en un niño con síndrome de Down, del sector “San Sebastián” período 2024 – 2025 - Rogel Orosco, Mary Selena (2025)
This research is a case study on play strategies to improve psychomotor skills in a child with Down syndrome, from the “San Sebastián” sector. For this reason, the general objective was to determine the influence that play strategies have on the psychomotor skills of a child with Down syndrome, with three specific objectives: to evaluate the psychomotor skills of a child with Down syndrome; to identify which strategies are used by the family and teachers to promote psychomotor skills in the child with Down syndrome; to design a play strategies guide as an alternative proposal to promote psychomotor skills in the child with Down syndrome; and to evaluate the effectiveness of the play strategies guide in the child with Down syndrome. The present research was developed through a quali-quantitative approach, descriptive, with a transversal non-experimental design, among the methods applied were scientific, descriptive, analytical-synthetic, inductive-deductive and correlational. For the empirical data collection process, techniques such as interview, survey and standardized scale were prioritized. The instruments used were a semi-structured interview with semi-structured questions directed to the mother, a multiple-choice survey directed to the teachers and the psychomotor evaluation scale applied to the case study child. In the study, 4 teachers, 1 mother and 1 case study child were delimited as a representative sample. The results reveal that the child with Down syndrome has a low level in the psychomotor profile. Deriving a main conclusion, that the difficulties in psychomotor skills cause problems in the development of autonomy when performing school activities, as well as activities of daily living in the case studied. For this, it is proposed to implement the use of games as ludic strategies in the development of motor skills